Eccentric harmonic index of a graph. Issue 1 (2nd January 2019) - Sowaity, M. I.; Pavithra, M.; Sharada, B.; Naji, A. M.
Abstract: In this paper, we introduce the eccentric harmonic index H e = H e ( G ) of a graph G, so that it is the sum of the terms 2 e i + e j for the edges v i v j, where ei is the eccentricity of the i th vertex of the graph G . We compute the exact values of He for some standard graphs. Bounds for He are established. Relationships between He and the eccentric connectivity index ξ c ( G ) are derived.